Interior Holder Regularity and Infinite Time Extinction to a doubly Nonlinear Degenerate Parabolic Equations of Signed Solutions - Sarkar, Md Abu Hanif (GANIT: Journal of Bangladesh Mathematical Society, 2023)
We study doubly nonlinear parabolic equation with sign changing solutions. We established the Holder regularity and the infinite time extinction of it within a parabolic domain. GANIT J. Bangladesh Math. Soc. 43.1 (2023) 75- 91